2013
DOI: 10.1130/ges00879.1
|View full text |Cite
|
Sign up to set email alerts
|

Orogenic to postorogenic (1.20-1.15 Ga) magmatism in the Adirondack Lowlands and Frontenac terrane, southern Grenville Province, USA and Canada

Abstract: Magmatism in the southern GrenvilleProvince records a collisional and postcollisional history during the period 1.20-1.15 Ga in the Adirondack Lowlands (New York State, USA) and the Frontenac terrane (Ontario, Canada). The 1.20 Ga bimodal Antwerp-Rossie suite of the Adirondack Lowlands was produced by subduction in the Trans-Adirondack backarc basin. This was followed by intrusion of the 1.18 Ga alkalic to calc-alkalic Hermon granite, which may have been generated by melting of metasomatized mantle during coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 66 publications
(150 reference statements)
0
8
0
Order By: Relevance
“…Closure of the Trans-Adirondack backarc basin, tectonic juxtaposition of the Frontenac and Adirondack Lowlands domains, obduction of an ophiolite complex with its sedimentary cover onto the Adirondack segment, and accretion of the Adirondack Belt to Laurentia took place in the ca. 1200-1160 Ma Shawinigan orogeny (e.g., Chiarenzelli et al, 2010;Peck et al, 2013;Fig. 3).…”
Section: Late Mesoproterozoic Tectonic History Of Laurentiamentioning
confidence: 99%
“…Closure of the Trans-Adirondack backarc basin, tectonic juxtaposition of the Frontenac and Adirondack Lowlands domains, obduction of an ophiolite complex with its sedimentary cover onto the Adirondack segment, and accretion of the Adirondack Belt to Laurentia took place in the ca. 1200-1160 Ma Shawinigan orogeny (e.g., Chiarenzelli et al, 2010;Peck et al, 2013;Fig. 3).…”
Section: Late Mesoproterozoic Tectonic History Of Laurentiamentioning
confidence: 99%
“…4, Edwardsville, E and Canton, C) and have been correlated with AMCG rocks in the AHT (McLelland et al 1988). Peck et al (2011Peck et al ( , 2013 have shown that the geochemical properties of the Edwardsville pluton link its source rocks to the Frontenac Terrane, which may comprise the underlying deep crust in the westernmost ALT. Note that none of the ca.…”
Section: Geology Of the Adirondack Mountainsmentioning
confidence: 99%
“…Early Stenian sources are rare within both Grenvillian and Sveconorwegian orogens in general. Potential southern sources are from the Adirondack Mountains and the Frontenac terrane in the Grenville Orogen (e.g., McLelland et al 2004, Peck et al 2013, and the Telemarkia and Bamble-Kongsberg terranes in the Sveconorwegian Orogen (Bingen & Solli 2009). However, the early Stenian magmatic suites in the Grenville Orogen are hosted within a regional setting that was dominated by Ectasian tectonic activity (e.g., Hanmar et al 2000).…”
Section: Discussionmentioning
confidence: 99%